1996
DOI: 10.1007/bf02331433
|View full text |Cite
|
Sign up to set email alerts
|

In situ heterogeneity of peroxisomal oxidase activities: An update

Abstract: Oxidases are a widespread group of enzymes. They are present in numerous organisms and organs and in various tissues, cells, and subcellular compartments, such as mitochondria. An important source of oxidases, which is investigated and discussed in this study, are the (micro)peroxisomes. Oxidases share the ability to reduce molecular oxygen during oxidation of their substrate, yielding an oxidized product and hydrogen peroxide. Besides the hydrogen peroxide-catabolizing enzyme catalase, peroxisomes contain one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 294 publications
(225 reference statements)
1
21
0
Order By: Relevance
“…Unlike peroxidase, catalase is localized mainly to the peroxisomes of photosynthetic plant cells, and is the marker enzyme for them. It takes an active part in neutralization of hydrogen peroxide and (primarily) superoxide to water (van Den Munckhof, 1996). The joint effect of catalase and peroxidase helps to ease the effect of ROS in plants invaded by insects.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike peroxidase, catalase is localized mainly to the peroxisomes of photosynthetic plant cells, and is the marker enzyme for them. It takes an active part in neutralization of hydrogen peroxide and (primarily) superoxide to water (van Den Munckhof, 1996). The joint effect of catalase and peroxidase helps to ease the effect of ROS in plants invaded by insects.…”
Section: Discussionmentioning
confidence: 99%
“…Live cells were irradiated in the presence of substrate [(3-amino-9-ethylcarbazole (AEC) or 3,3Ј-diaminobenzidine (DAB)] but without exogenous H 2 O 2 . Reaction product (polymerized substrate) was expected wherever H 2 O 2 was produced in proximity to endogenous catalase, peroxidase, and/or oxidase (28). DAB stock solution (10 mg/ml; Electron Microscopy Sciences, Ft. Washington, PA) was prepared in DMSO (Aldrich) and diluted 1:1,000 in saline for use.…”
Section: Methodsmentioning
confidence: 99%
“…However, ultrastructural examination of many different areas of the brain gives strong indication of a particulate CuZnSOD as well. We first interpreted these vescicles as peroxisomes on the basis of their size and morphology; even the dishomogeneous immunostaining observed within these organelles is in keeping with their peroxisomal nature, because a subcompartmentalization of peroxisomal enzymes has been largely demonstrated (for review see Van Den Munckhof 1996). Postembedding double immunogold labeling confirmed that the CuZnSOD-positive particles are true peroxisomes.…”
Section: Cuznsod As a Peroxisomal Enzymementioning
confidence: 96%